Robust state-derivative pole placement LMI-based designs for linear systems - Faria, F.A.; Assunção, E.; Teixeira, M.C.M.; Cardim, R.; da Silva, N.A.P. (International journal of control, 2009)
In some practical problems, for instance in the control systems for the suppression of vibration in mechanical systems, the state-derivative signals are easier to obtain than the state signals. Necessary and sufficient LMI-based conditions for pole placement of linear systems using state-derivative feedback are proposed. Sufficient conditions for pole placement for a class of uncertain systems or systems subject to structural failures are also presented. The simulation of practical applications illustrates the efficiency of the proposed methods.